Aerodynamic performance of a bird-inspired morphing tail - Yuta MURAYAMA; Toshiyuki NAKATA; Hao LIU (Journal of Biomechanical Science and Engineering, 2022)
Flying animals such as insects, bats, and birds have acquired the ability to achieve diverse and robust flight patterns in various natural environments. Their sophisticated morphologies, kinematics, and dynamics have motivated engineers to develop bioinspired flying robots. Particularly, the capabilities of morphing wing and tail controls in birds have received significant attention. Such controls are expected to introduce novel mechanisms to achieve flight stabilization while maintaining high maneuverability with a low energy cost. While the control of tail posture and motion is considered to exhibit a significant influence on flight performance, there have been few studies focusing on control with multiple degrees of freedom in small flying robots. In this study, we developed a bird-inspired morphing tail mechanism; a model was fabricated and investigated its aerodynamic performance through wind tunnel experiments. The results indicate that the tail attitude can be controlled effectively to enable the enhancement of aerodynamic performance in terms of mechanical efficiency and controllability. We also verified that controlling the tail attitude is redundant in the control of aerodynamic force and moment production, implying the potential capability to achieve stable flight control strategies in response to various disturbances. Therefore, our results indicate that tail-attitude-based aerodynamic control may be able to cope with the conflicting requirements of improving stability and maneuverability of flyers.